The Role of Authentic Leadership in Work Life Balance and Employee Performance with Mediated Employee Engagement - Yasmin, Humaira Putri; Rahmawati, Rini (PT Mattawang Mediatama Solution, 2025)
Leadership approaches in public sector organizations face distinct challenges in promoting work‒life balance and performance while maintaining employee engagement. Authentic leadership has emerged as a promising framework for addressing these challenges; however, limited research has examined its effectiveness within Indonesian government institutions. This study examines the influence of authentic leadership on work‒life balance and employee performance, with employee engagement as a mediating variable at the Department of Communication and Information Technology (Diskominfo) in Banjarbaru city, Indonesia. Using a quantitative approach with a causal design, this study surveyed 64 employees through a saturation sampling method. The data were analyzed via structural equation modeling-partial least squares (SEM‒PLS) to evaluate both direct and indirect relationships among the variables. Authentic leadership positively influenced work‒life balance (β=0.618, t=5.934, p<0.001) and employee performance (β=0.683, t=9.439, p<0.001). Employee engagement mediated the relationships between authentic leadership and work-life balance (β=0.656, t=6.112, p<0.001) and between authentic leadership and employee performance (β=0.632, t=4.682, p<0.001). The indirect effects of employee engagement (0.454 for work‒life balance; 0.471 for performance) were stronger than the direct effects (0.147 for work‒life balance; 0.229 for performance), confirming the partial mediating role of employee engagement. Authentic leadership significantly enhances work‒life balance and employee performance in public sector organizations, primarily by strengthening employee engagement. Government institutions should prioritize the development of authentic leadership capabilities and the implementation of policies that support employee engagement to optimize both organizational performance and employee well-being.